Optimasi Kombinasi Asam Sitrat dan Asam Tartrat sebagai Zat Pengasam pada Tablet Effervescent Ekstrak Ubi Jalar Ungu (Ipomoea batatas L) - Dahlia Syahrina; Noval Noval (Jurnal Surya Medika (JSM), 2021)
Purple sweet potato has the content of anthocyanin compounds that are efficacious as antioxidants. To deliver these efficacious compounds, formulations of effervescent tablets are required as antioxidants with a combination of citric acid and tartrate acid to accelerate the solubility of the drug. The research aims to optimize the combination of citric acid and tartrate acid as a sourgent on effervescent tablets of purple sweet potato extract using the simplex lattice design method. The manufacture of tablets using a direct pumping method with effervescent powder evaluation includes flow rate test, silent angle, compressibility, and powder moisture. Evaluation of tablets includes organoleptic tests, uniformity of tablet weight, hardness, fragility, and soluble time of tablets—data analysis using simplex lattice design software design expert version 10. The results of effervescent powder evaluation include a test of flow rate, quiet angle, compressibility, and moisture of powder in each formula that already meets the requirements. The physical evaluation results on the effervescent tablet weight uniformity test on F3, F4, and F5 have met the requirements. The evaluation of tablet hardness F1 and F2 also meet the requirements. The results of the evaluation of fragility and time dissolve tablets have met the requirements of all formulas. The simplex lattice design analysis results obtained F5 as the most optimal formula with a concentration of citric acid 103.25 mg and tartrate acid 44.25 mg. The combination of citric acid and tartaric acid affects the evaluation of hardness, fragility, and time-soluble effervescent tablets of purple sweet potato extract. The optimal concentration based on simplex lattice design analysis was obtained in F5 with a citric acid concentration of 103.25 mg and tartrate acid of 44.25 mg.